Compatibilización de equipos de microscopía virtual: análisis de alternativas con software de imágenes panorámicas. - Alfaro, Luis; Poblet, Enrique; Catalá, Pablo; Navea, Amparo; García-Rojo, Marcial (Revista Española de Patología)
The use of virtual microscopy equipment has been limited by its high cost or the lack of standardization of the software from different manufacturers. In order to find alternative programmes that could be easily used with existing equipment and therefore avoid the cost of specific software, we analyzed the following five panoramic image software suitable for virtual microscopy: Zoomify, HDView, Gigapan, Silverlight Deep Zoom and Google Earth. With only minor differences, all of these programmes were found to be potentially adaptable for microscopic images and were simple to use in the building of web links accessible from any internet connection. None require computer programming and the pathologist can use them without technical assistance, although a certain knowledge of digital imaging, web server management and web design optimizes their performance with virtual microscopy.